2008
DOI: 10.1080/02671520802308677
|View full text |Cite
|
Sign up to set email alerts
|

Transition matters: pupils’ experiences of the primary–secondary school transition in the West of Scotland and consequences for well‐being and attainment

Abstract: The importance of school transitions for pupil adjustment, particularly their impact on later well-being and attainment, remains contested. This paper draws on data from a longitudinal, school-based study of over 2000 Scottish pupils, first surveyed in 135 primary schools (age 11) in 1994, and followed up in 43 secondary schools (age 13 and 15) and again after leaving school (age 18/19) in 2002/3. The length of follow-up makes this study unique in transition research.After a year in secondary school (age 13), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
268
7
28

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(316 citation statements)
references
References 38 publications
(70 reference statements)
13
268
7
28
Order By: Relevance
“…Whereas earlier research has shown correlations between being bullied and psychosocial problems (e.g. Aluede et al 2008;Hawker and Boulton 2000;Rigby 2003;Roland 2002;West, Sweeting, and Young 2010), the current study contributes to this research body by portraying the psychosocial processes from the victims' point of view, which could, at least in part, describe and explain the link between being bullied and these psychosocial problems.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Whereas earlier research has shown correlations between being bullied and psychosocial problems (e.g. Aluede et al 2008;Hawker and Boulton 2000;Rigby 2003;Roland 2002;West, Sweeting, and Young 2010), the current study contributes to this research body by portraying the psychosocial processes from the victims' point of view, which could, at least in part, describe and explain the link between being bullied and these psychosocial problems.…”
Section: Discussionmentioning
confidence: 93%
“…Aluede et al 2008;Hawker and Boulton 2000;Rigby 2003;Roland 2002). For example, West, Sweeting, and Young (2010) found that being a victim of bullying at age 11 correlated with depression symptoms at ages 13 and 15.…”
mentioning
confidence: 99%
“…However, the authors argue (in accordance with the present findings) that the academic ability self-concept plays a relevant moderating role, insofar as critical life-events are more likely to be experienced positively when individual resources are high . If students do not believe in their academic ability, the likelihood of experiencing the transition as a threat is enhanced and thus the likelihood of positive emotions is reduced (see also West, Sweeting, & Young, 2010).…”
Section: The Emotional Valence Of the Upcoming Transitionmentioning
confidence: 99%
“…The differences in the positive or negative valence in emotions can be traced back to intra-individual differences among students, such as their academic or social self-concepts which can have an effect on the control cognitions, termed as "secondary appraisal" by Lazarus (2001) and thus on the emotional quality (e.g. Wargo Aikins, Bierman, & Parker, 2005;West, Sweeting, & Young, 2010). Apart from factors related to the individual learner, environmental conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Mahon and Robinson 2011, Held 2006, and it is within this framework we understand that transition from primary to secondary school education (moving from year 6 to 7) can be challenging and care-less, especially for disabled children and their families , Holt 2004a, West, Sweeting and Young 2008. By interrogating narratives of parents and professionals, we are able to explore transitions and self-identity in multifarious ways, as arguably a meaningful transition depends on the care-full spaces disabled pupils inhabit, and those 'doing' caring work have a significant part to play (Pyer et al 2010).…”
Section: Introductionmentioning
confidence: 99%